Compliance – Its Purpose, Scope, and Protection Instruments - Janik , Andrzej (Studia Ecologiae et Bioethicae, 2020)
In common practice, compliance means acting in accordance with the law and ethics. This applies to business activities, especially the regulated (supervised) ones, but also to the public sector. In both areas, there appear to be special units in the internal structure of the organisation, dedicated to compliance supervision. They are either mandatory - in supervised industries, this refers in particular to financial services - or voluntary, if the scale and the significance of the organisation justify their existence. The legally prescribed rules on the organisation and operation of compliance in supervised entities, undoubtedly set the pattern for firms in other branches. The regulatory instruments of compliance are mainly of a procedural nature. The subject-matter of the protection is not compliance itself, but rather primary goods and values such as the environment, equality, dignity, solidarity. The last one comes to the fore, especially, in the context of the widely spread – and reprehensible – tax avoidance practices through allocation of assets to the so-called tax paradises. Making use of the resources and infrastructure of the country where business operations are conducted, is accompanied by none, or by hardly any levies for its benefit. The starting point for compliance was a set of high-profile cases, disclosed through what is popularly known as “whistleblowing”, which fuelled the idea of introducing compliance as a primary issue for corporate organisations. That function requires some special guarantees, protecting the “whistle blower”, and the person that is being incriminated. In the broader context, compliance has become a component part of corporate governance, or of its softer form, “good practices”.